Intellectual Capital in German Non-profit Organisations An Empirical Study - Blankenburg, Katrin (Contributions to Management Science,, 2018)
This book describes how non-profit organisations (NPOs) communicate what they constitute, signal success and display sustainability in order to convince stakeholders to provide essential resources. Reports on intellectual capital offer a worthwhile approach. Based on empirical research, the book highlights the essential resources for NPOs and on the demand imposed on organisations, as well as the dependencies of those resources and demands. This insight helps NPOs to provide necessary information while keeping the disclosure to a minimum and thus not giving away possible competitive advantages. Further, the status-quo of IC disclosure in Germany is presented and a theoretical framework for the motivation for NPOs to disclose information on their IC is presented. Researchers will find these findings a solid foundation for further research. Finally, a framework for the disclosure of intellectual capital is provided to support practitioners.